Metal complexes of novel Schiff base derived from iron sandwiched organometallic and 4‐nitro‐1, 2‐phenylenediamine: Synthesis, characterization, DFT studies, antimicrobial activities and molecular docking. (13th February 2018) - Mahmoud, Walaa H.; Deghadi, Reem G.; Mohamed, Gehad G.
Abstract : The condensation of 2‐acetylferrocene with 4‐nitro‐1, 2‐phenylenediamine in a 1:1 molar ratio, resulting in formation of a novel bi‐dentate organometallic Schiff base ligand (L), (2‐(1‐((2‐amino‐5‐nitrophenyl)imino)ethyl)cyclopenta‐2, 4‐dien‐1‐yl)(cyclopenta‐2, 4‐dien‐1‐yl)iron. Also, its Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) complexes have been synthesized. The stoichiometric ratios of the prepared compounds were estimated using elemental analysis (C, H, N, M), molar conductivity, FT‐IR, UV‐Vis, 1 H‐NMR, SEM and mass spectral analysis. Furthermore, their TG and DTG properties were studied. The geometrical structure of the complexes was found to be octahedral. From spectral analysis, the Schiff base coordinated to metal ions through the azomethine and amine groups. DFT‐based molecular orbital energy calculations of the synthesized ligand have been studied, in which the ligand was theoretically optimized. The Schiff base and its metal complexes have been screened for their antimicrobial activities against different bacterial and fungal species by using disc diffusion method. The anticancer activities of the ligand and its metal complexes have also been studied towards breast cancer (MCF‐7) and human normal melanocytes (HFB‐4) cell lines. Molecular docking was also used to identify the interaction between the Schiff base ligand and its Cd(II) complex with the active site of the receptors of breast cancer mutant oxidoreductase (PDB ID: 3HB5), crystal structure of Staphylococcus aureus (PDB ID: 3Q8U) and yeast‐specific serine/threonine protein phosphatase (PPZ1) of Candida albicans (PDB ID:5JPE). Abstract : Schiff base ligand derived from iron sandwich.